Viral etiology of severe acute respiratory infections in hospitalized children in Cameroon, 2011–2013. Issue 5 (9th May 2016) - Kenmoe, Sebastien; Tchendjou, Patrice; Vernet, Marie‐Astrid; Moyo‐Tetang, Suzie; Mossus, Tatiana; Njankouo‐Ripa, Mohamadou; Kenne, Angeladine; Penlap Beng, Véronique; Vabret, Astrid; Njouom, Richard
Abstract : Background: Severe acute respiratory illness (SARI) is recognized as an important cause of morbidity, mortality, and hospitalization among children in developing countries. Little is known, however, in tropical countries like Cameroon about the cause and seasonality of respiratory infections, especially in hospitalized settings. Objectives: Our study investigates the viral etiology and seasonality of SARI in hospitalized children in Yaounde, Cameroon. Methods: Prospective clinic surveillance was conducted to identify hospitalized children aged ≤15 years presenting with respiratory symptoms ≤5‐day duration. Demographic and clinical data, and respiratory specimens were collected. Nasopharyngeal samples were tested for 17 respiratory viruses using a multiplex polymerase chain reaction. The viral distribution and demographic data were statistically analyzed. Results: From September 2011 through September 2013, 347 children aged ≤15 years were enrolled. At least one virus was identified in each of 65·4% children, of which 29·5% were coinfections; 27·3% were positive for human adenovirus (hAdV), 13·2% for human respiratory syncytial virus (hRSV), 11·5% for rhinovirus/enterovirus (RV/EV), 10·6% for human bocavirus (hBoV), 9·8% for influenza virus (Inf), 6·6% for human parainfluenza virus (hPIV), 5·7% for human coronavirus (hCoV), and 2·3% for human metapneumovirus (hMPV). While hRSV showed seasonal patterns, hAdV and RV/EV were detected throughout the year and no evident temporal patterns were observed for the remaining viruses. Conclusion: Respiratory viruses were associated with a high burden of hospitalizations among children in Cameroon. Nevertheless, additional studies evaluating asymptomatic Cameroonian children will be important in understanding the relationship between viral carriage and disease.